2019
DOI: 10.1519/jsc.0000000000002186
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Two Interval Shuttle-Run Training Modes on Physiological and Performance Adaptations in Female Professional Futsal Players

Abstract: The purpose of the present study was to analyze the effects of two shuttle-run interval training (SRIT) models with one and three directional changes per running bout on the aerobic and anaerobic performances of elite female futsal players. Sixteen players competing in the Brazilian National Division League took part in the study. The training protocols consisted of shuttle-run intervals organized in four sets of 4-min bouts with 3- min of rest intervals between the sets. The SRIT models were composed of one (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 43 publications
1
24
0
1
Order By: Relevance
“…On the contrary, improvements in repeated sprint performance through aerobic high-intensity training might be associated with the training period during the preseason. Recently, Teixeira et al [ 29 ] reported that high-intensity aerobic training involving shuttle-run intervals (4 × 4 min) for five weeks during the preseason enhanced repeated sprint ability with increased aerobic performance in elite athletes. When considered, these findings suggest that more than three weeks of high-intensity aerobic training is required to develop repeated sprint performance during preseason in elite players.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, improvements in repeated sprint performance through aerobic high-intensity training might be associated with the training period during the preseason. Recently, Teixeira et al [ 29 ] reported that high-intensity aerobic training involving shuttle-run intervals (4 × 4 min) for five weeks during the preseason enhanced repeated sprint ability with increased aerobic performance in elite athletes. When considered, these findings suggest that more than three weeks of high-intensity aerobic training is required to develop repeated sprint performance during preseason in elite players.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, all three field playing positions (e.g., guards, wingers, pivots) must be able to effectively change their positions during the game, which actually accentuate the necessity for their agility performance. In other words, irrespective of their primary game specific tasks (i.e., defender—keeping the ball, making the smart passes; winger—sprinting and passing; pivot [topman]—attacking and scoring), all futsal players must possess exceptional agility with and without the ball [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to soccer, futsal players perform more changes of direction during a game, while dribbling a smaller ball across a reduced court size [26]. For these reasons, both CODS and RAG may be especially important physical fitness parameters in futsal [25,26], and hence specific research within the sport is needed. However, no study so far has examined tests of agility-components that involved dribbling with the ball in this sport.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, for MLSS and all derived parameters during the T-Car test, HR values were above 85 % of HRmax (▶ Table 1). Likewise, a previous study showed that interval sessions in shuttle run mode, at submaximal intensities (86 and 89 % of sPeak), were an effective strategy for improving maximum and submaximal indices in elite futsal athletes [35]. However, that study [35] used another intermittent incremental test (i. e. FIET) and not T-Car; therefore, investigations are necessary regarding the use of submaximal variables derived from T-Car for training prescription.…”
Section: Discussionmentioning
confidence: 98%